Specificity and Sensitivity of the Streptozyme Test for the Detection of Streptococcal Antibodies - Kholy, Aziz El (1974)
A comparison between the results of the streptozyme hemagglutination test and serological titers for anti-streptolysin O (ASO), anti-hyaluronidase (AH), anti-deoxyribonuclease B (ADN-B), and anti-nicotinamide adenine dinucleotidase (ANAD) was made in two groups of human sera. In one group, serological titers for all the four antibodies were lower than the threshold of sensitization reported by the producing firm. In the second group, the titer of at least one of the four antibodies was equal to or higher than the threshold. False-positive and false-negative reactions occur with those sera when one or more antibody titer is at or near the threshold of the test as described by the manufacturer. The test was positive for all sera where either the ASO was greater than 166 or the ANAD was greater than 270, and for 98% of the sera with ADN-B greater than 360. It is, therefore, concluded that the streptozyme test can be used as an adjunct to the clinical diagnosis of streptococcal infections and their nonsuppurative sequelae. It is less useful to assess the levels of antibodies in sera from general population surveys. For such sera, the relative specificity and sensitivity of the test might yield misleading results. Until more experience is gained with the test, caution should be used in its application to infant and older adult age groups, where significant streptococcal antibody titers are frequently near the threshold of the test.